Symptom management in adult brain tumours: A literature review - Rong Zhang; Dong‐Mei Wang; Yong‐Li Liu; Man‐Li Tian; Ling Zhu; Jing Chen; Jun Zhang (Wiley, 2023)
Abstract Aim To review the literature related to symptom management, clinical significance and related theoretical framework systems in adult patients with brain tumours. Background As understanding of symptoms or symptom clusters and underlying biologic mechanisms has grown, it is apparent that symptom science is moving forward. Although some progress has been made in the symptom science of solid tumours such as breast and lung neoplasms, insufficient attention has been paid to symptom management for patients suffering from brain tumours. Further research is needed to achieve effective symptom management for these patients. Design A literature review with a systematic search of symptom management in adult brain tumours. Methods Electronic data bases were searched to obtain relevant published literature on symptom management in adults with brain tumours. This was then analysed and a synthesis of relevant findings is presented. Findings Four significant general themes relating to symptom management of brain tumours in adults were identified: (1) The potential theoretical foundation related to symptom management was revealed. (2) Widely accepted validated scales or questionnaires for the assessment of single symptoms or symptom clusters were recommended. (3) Several symptom clusters and the underlying biologic mechanisms have been reported. (4) Specific symptom interventions for adults with brain tumours were collected and classified as evidence‐based or insufficient evidence. Conclusion There are still many challenges in the effective management of symptoms in adults with brain tumours. The guiding role of theoretical frameworks or models related to symptom management should be utilized in future research. Using the concept of symptom clustering for research into symptoms found in patients with brain tumours, exploring common biological mechanisms for specific symptom clusters and making full use of modern big data resources to build a strong evidence base for an effective intervention or management program may inform the management of symptoms among these patients leading to better results. No Patient or Public Contribution This is a literature review. Implications for Symptom Management The ultimate goal is obviously not only improving the survival rate of patients with brain tumours, but also enhancing their quality of life. Several important findings from our review include the theoretical foundations, validated assessment tools, the assessment of symptom clusters and the underlying biologic mechanism, and the identification of the evidence base for symptom interventions. These are of relevance for managers, researchers and practitioners and may function as a reference to help the effective symptom management for adults with brain tumours.